A Brief Primer on Enhancing Islamic Cultural Competency for Deploying Military Medical Providers. Issue 1 (2nd January 2022) - Bagasra, Anisah; Moore, Brian A.; Judkins, Jason; Buchner, Christina; Young-McCaughan, Stacey; Foral, Geno; Ojeda, Alyssa; Baker, Monty T.; Peterson, Alan L.
ABSTRACT: The contemporary operating environment for deployed United States military operations largely focuses on deployments to predominantly Islamic countries. The differences in cultural values between deployed military personnel and the citizens of these Islamic countries present a unique challenge to military personnel, especially when offering medical care. Cultural competency provides insights that can greatly increase the effectiveness of any military operation. Recent research indicates deployed military medical providers desire increased opportunities for cultural competency training prior to deployment. This primer provides an overview of religious values such as qadr —the belief that Allah has willed for something to happen—and of the Islamic belief that Allah has placed individuals to be caretakers of their bodies. It also highlights the impact of religio-cultural norms as important factors influencing medical decisions and health behaviors. Enhanced understanding of these principles can greatly improve the efficacy of patient care when consulting with and caring for Muslims who may be conflicted about receiving medical care from a non-Muslim. As military medical personnel become more culturally informed when preparing for deployment, they increase the likelihood of establishing positive relationships and providing effective medical care.